THE ROLE OF THE ECONOMETRIC MODEL IN THE ANALYSIS OF INVESTMENT IMPACT ON GDP GROWTH IN THE FERGANA REGION - Akromjon Usmanov; Abdulvohid Kodirov (Ecominds Press, 2025)
Investments are universally recognised as one of the primary drivers of economic growth, directly contributing to the expansion of productive capacities, technological modernisation, and overall improvement in economic performance. Among the various macroeconomic indicators, Gross Domestic Product (GDP) remains the most comprehensive metric reflecting the scale and health of a country's economy. It captures the total monetary value of all final goods and services produced within a specific territory over a defined period. This article focuses on the Fergana region of Uzbekistan and aims to assess the correlation between investment activity and GDP growth from 2010 to 2023. Using an econometric approach, including autoregressive distributed lag (ARDL) models, the study analyses time-series data to uncover the short-term and long-term effects of capital investments on regional GDP performance. The research highlights key structural shifts in investment patterns, identifies the sectors with the most significant returns, and evaluates the lag effect of investments on economic output. The findings of the analysis provide valuable insights into the role of targeted investment policies in regional development and offer evidence-based recommendations for optimising investment strategies to enhance GDP growth at both regional and national levels. By applying modern econometric modelling, this study contributes to the academic discourse on economic forecasting, regional planning, and policy formulation.
Keywords: Fergana region; gross domestic product (GDP); investment analysis; autoregressive distributed lag model (ARDL); economic growth; time-series econometrics; investment policy; regional development; macroeconomic modelling; forecasting.